Convergence of Islamic and Conventional Interbank Rates (Global Journal of Management and Business Research, 2013)
Financial Institutions' (FI) and banks' earnings on the trading portfolio are significantly influenced by the changing market conditions such as price of an asset, interest rates, market volatility, and market liquidity. Researchers to measure the risk related uncertainty of the FI's earnings use few Market Risk Measurement Models (MRM). Historic Back Simulation Model is one of the approaches that consider the return on all assets, as non-normal, as against the RiskMetric Model that considers the returns on assets is symmetric. This paper investigates the risk and return associated with Islamic interbank offered rates (IIBOR) in Malaysia using Back Simulation model and the results are compared with the conventional interbank offered rates (CIBOR). On application of the Back Simulation approach over the two different data sets (Yield Rates of IIBOR and CIBOR), it was found that during the de-peg period, the value losses and gains for Islamic trading portfolios were found to be significantly higher at the tail end horizon depeg period. We also conducted independent sample "t" test to compare the mean losses and mean gains reported during these three time periods.
Keywords: interbank offered rate; back simulation; islamic finance products; volatility; value at risk